Poligami Sirri dalam Tinjauan Mashlahat - Sudirman, Sudirman; Dedi, Syarial; Saputra, Hasep (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2021)
The reason for opposing polygamy is because it is considered to have many negative effects and is considered to discriminate against women. While those who agree, argue that Islam does not prohibit polygamy, under certain conditions polygamy is one solution to overcome household problems. This research is a library research. So based on the results of the research the authors conclude that the sirri polygamy practiced by the community today does not contain mashlamat because: first, sirri polygamy is legally flawed, both religious law and state law; second, polygamy sirri does not achieve the purpose of marriage in sharia, namely so that human life in this world is full of peace and love; third, sirri polygamy is detrimental to women and their offspring.